Territorial Investigations - Balkema, Annette W.,; Slager, Henk, (European History and Culture - Book Archive pre-2000, 1999)
Nowadays there are many spaces of fascination in visual art. Of course, installative space and contextual space have been on the art scene for awhile. However, they are now accompanied by other spaces such as urban space, architectural space, cyberspace, hyperspace, and screen-based space. In this volume, architects, artists, theorists, three symposia and four exhibitions attempt to find answers to questions such as: Could the architectonic study and/or deconstruction of space play a decisive role in the shift of attention to space? Which theoretical factors structure the current experience and meaning of space? What is the role of the aesthetization of the environment on our concept of space? Smooth Space - VCC de Brakke Grond, Amsterdam - is a project at the heart of this publication. Spatial interests range from how the concept of space is redefined and exploited in our current visual culture to how the digital world influences our spatial concepts. Participants in this issue are: Jean Attali, Annette W. Balkema, Andrew Benjamin, Ole Bouman, Bernard Cache, Paul Crowther, Christoph Fink, Hugo Heyrman, Hou Hanru, Rem Koolhaas, Geert Lovink, Karlheinz Lüdeking, Bartomeu Mari, Kas Oosterhuis, Jan van de Pavert, Keiko Sato, Eran Schaerf, Lara Schnitger, Roger Scruton, Martin Seel, Nasrine Seraji, Henk Slager, Sjoerd Soeters, Lars Spuybroek, Ann Van Sevenant, Peter Weibel and Mark Wigley.